Empowering First-Grade Students’ Learning: Enhancing Education Through English E-Storybooks Aligned with The Emancipated Curriculum - Dhirapriyani, Kadek; Suprianti, G.A.P.; Budiarta, Luh Gd Rahayu (STKIP AGAMA HINDU SINGARAJA, 2024)
This research explores the development of English e-storybooks integrated with the Emancipated Learning curriculum for first-grade students at SDN 3 Banjar Jawa. Following the Design and Development (D&D) model, specifically the ADDE (Analyze, Design, Development, and Evaluation) framework, the study employs a mixed-method approach, combining qualitative and quantitative analyses. The research addresses the dearth of supplementary materials and the limited use of e-storybooks in the context of Emancipated Learning. The process involves a systematic analysis of needs, the design of a comprehensive blueprint, the development of e-storybooks, and an evaluation based on expert judgment, teacher assessments, and student feedback. The results indicate that the developed e-storybooks align with curriculum objectives and exhibit excellence in material development principles. The findings emphasize the potential of e-storybooks in enhancing language skills and supporting 21st-century learning principles. The research contributes valuable insights for educators, researchers, and curriculum developers interested in creating effective digital resources tailored to specific educational contexts.